2022-RA-1517-ESGO Wroclaw comprehensive cancer centre 100 months experience in cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS+HIPEC) in patients with peritoneal carcinomatosis – indications and complications of the procedure. (20th October 2022) - Szewczyk, Krzysztof; Jedryka, Marcin; Bebenek, Marek
Abstract : Introduction/Background: Selected patients with peritoneal dissemination of gastrointestinal (colorectal and gastric cancer), ovarian and primary peritoneal cancers benefit from cytoreductive surgery (CRS) combined with intraperitoneal chemotherapy in hyperthermia (HIPEC). In Poland, only a few oncology centers regularly perform CRS+HIPEC procedures, while the demand for them has been set at a minimum of 2000 per year (Nowotwory Journal of Oncology 2014; 64, 6: 518–524). The aim of the study was the analysis of number, indications and complications of CRS+HIPEC procedures analysis performed in the 1st Oncological Surgery Department of Wroclaw Comprehensive Cancer Center (WCCC), Poland, during the first 100 months of the procedure. Methodology: Demographic, clinical, oncological and technical aspects database of all WCCC patients undergoing CRS+HIPEC procedure was created. Data statistical analysis was performed with Statistica version 12.5 (StatSoft). Results: In the period from 01.2014 to 04.2022, a total of 232 CRS+HIPEC procedures were performed at WCCC, 28 per year on average (range 20–37). The indications were mainly ovarian (40%) and colorectal (39%) cancers, followed by peritoneal pseudomyxoma (7%), peritoneal mesothelioma (6%), gastric (3%) and other cancers (5%). The scope of surgical cytoreduction (CRS) was wide: from single peritoneal nodules to extensive multi-organ radical (CC-0) or almost radical (residuals up to 2.5 mm – CC-1) resections. All HIPEC procedures were performed in closed technique. Clavien-Dindo grade III and IV complications occurred in 14% of patients. There were no perioperative deaths recorded. Conclusion: CRS+HIPEC procedures are rarely performed, however safe and promising therapeutic option for different patients with primary and secondary peritoneal cancers.